주요국의 임산부 및 신생아 진료협력체계 구축 현황 비교 - 현유림; Yoorim Bona Hyun; 김송이; Songyi Kim; 최지숙; Ji-sook Choi (HIRA Research, 2024)
The number of births in South Korea is continuously decreasing, while the proportion of high-risk pregnancies is increasing. The South Korean government has implemented various policies to address the issue of declining childbirthrelated infrastructure, which remain unresolved. In response, the need for an innovative maternal health delivery system has been raised. This study aimed to derive implications for the introduction of policies to activate the delivery system by establishing a domestic maternal and newborn care cooperation systems. The performance and limitations of the maternal and child healthcare cooperation systems in Japan, the United Kingdom, Australia, and Canada were analyzed in this study. Regular meetings were conducted among medical institutions associated with local governments in each region in Japan along with efforts to maintain cooperation between medical institutions and local governments. A maternal and child health network that categorized pregnant women based on case severity and enabled management from the prenatal to postnatal period was established in the UK. Hospitals participating in the Australian network were providing clinical advice, training, and education as well as developing clinical guidelines; however, no separate compensation was allocated for network activities. In Canada, the principal operator of networks were general practitioners, and incentives were provided as a means to encourage their participation. Reflecting on the foreign cases, South Korea will be able to maintain continuous support for integrated treatment centers for managing high-risk pregnancies and neonates while considering ways to initiate treatment cooperation between institutions based on the type of medical institution. This will help in securing subsidies for treatment cooperation networks and compensation for participation, similar to that available in the global scenario.